LC acousto-optical transducer for nondestructive holographic control systems - Oleksenko, P.; Sorokin, V.; Zelinskyy, R.; Tytarenko, P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The construction of acousto-optical display based on the hysteretic in cholesteric liquid crystals (CLCs) is proposed for nondestructive holographic test systems. The influence oblique reactive sputtering deposited thin films of In₂O₃, AlxOy, SiOx, upon alignment properties of CLC, which are used as ultrasonic holographic recording media, is investigated. The technical characteristics and properties of developed acousto-optical display (AOD) are represented. The high sensitivity and planar texture reproducibility CLC are shown to be implicit advantages of AOD developed.